2002
DOI: 10.1097/00005537-200207000-00015
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Epoetin Alfa on Transfusion Requirements in Head and Neck Cancer Patients: A Prospective, Randomized, Placebo‐Controlled Study

Abstract: In this single institution study, we demonstrated a significant improvement in hematopoietic parameters and a trend toward decreased transfusion requirements using perioperative epoetin alfa in a head and neck cancer patient population. Further studies may delineate additional benefits in treating qualified patients with epoetin alfa during therapy for head and neck malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 60 publications
(85 reference statements)
1
31
1
Order By: Relevance
“…2,21 In our study, neither tumor size nor nodal status was correlated with the Hb decrease. Twenty percent of patients with T1-T2 tumors had an Hb decrease of B38 g/l, whereas 26% of the patients with T3-T4 an Hb decrease of [38 g/l.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…2,21 In our study, neither tumor size nor nodal status was correlated with the Hb decrease. Twenty percent of patients with T1-T2 tumors had an Hb decrease of B38 g/l, whereas 26% of the patients with T3-T4 an Hb decrease of [38 g/l.…”
Section: Discussioncontrasting
confidence: 78%
“…Moreover, numerous studies pointed out that low hemoglobin (Hb) levels before and during radiation therapy (RT) were associated with worse local control and survival in the various types of cancer. [1][2][3] Head and neck cancer patients are at high risk for developing anemia. Extensive radical surgery, being one of the important reasons, may cause high intraoperative blood loss.…”
mentioning
confidence: 99%
“…Clinical trials with erythropoietin and acute normovolaemic haemodilution have shown promising results in the reduction of allogenic blood product requirements in maxillofacial surgery; however, the importance of the meticulous surgical technique cannot be overemphasised (Scott et al, 2002;Habler et al, 2004). Clinicians must be cognizant of the 3 unit threshold and should attempt to limit transfusion volume whenever it is safe to do so.…”
Section: Discussionmentioning
confidence: 99%
“…The search obtained 6 eligible studies from 5 articles (22)(23)(24)(25)(26), which enrolled a total of 595 patients. The change in HB was reported in 2 studies (23,26), the transfusion requirements were noted from 3 studies (23,25), the ratio of transfusion was obtained from a total of 233 of 495 patients from 5 studies (22)(23)(24)(25)(26) and the change in HCT was reported in 2 studies (23,26). Table I presents the clinical characteristics from all studies.…”
Section: Resultsmentioning
confidence: 99%